PENGELOLAAN PERPUSTAKAAN SEBAGAI SARANA PEMBELAJARAN DI SD NEGERI NOGOTIRTO GAMPING SLEMAN - Prasetya, Alifudin; Siti Maisaroh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the process of library management as a learning facility at SD Negeri Nogotirto Gamping Sleman. The aspects studied are: 1) Planning, 2) Organizing, 3) Implementation, and 4) Evaluation. This research uses a qualitative approach with the subjects being the principal, teachers, and library staff. Data collection techniques include observation, interviews, and documentation. The data analysis techniques consist of data collection, data reduction, data presentation, and drawing conclusions. Data validity was tested using technique triangulation and source triangulation. The results of the study show: 1) In the planning aspect, the school has adhered to national library standards and refers to the School Activity Budget Plan (RKAS) in procuring facilities and infrastructure, although there is a need to add book collections according to the students' needs. 2) In the organizing aspect, the library is managed by one staff member who has full responsibility, but there is no formal organizational structure in place. 3) The implementation of library management is quite good, although training for staff has not been continued after the COVID-19 pandemic. 4) Evaluation is conducted periodically, involving library staff in assessing the condition of the book collection and the quality of student literacy, but student involvement in providing feedback needs to be improved. It is hoped that the results of this study can serve as a reference to improve the quality of library management, especially in the aspects of organization, training, and evaluation.